Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Di Negara G20 Dengan Research And Development (R&D) Sebagai Variabel Moderasi - Abdul Gani Laraga (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Economic growth is a concept used by a country to describe its economic condition. A country that has a level of economic growth indicates that the country has a good level of development and can be seen from its GDP per capita. This research aims to examine and analyze the correlation of labor, FDI, human capital on the economic growth of G20 countries in 2012-2021 by using Research and Development (R&D) as a moderating variable. This research uses Moderated Regression Analysis to determine the influence of Research and Development (R&D) used in the model and uses the Generalized Method of Moment (GMM) estimation technique. The test findings show that the labor, FDI and human capital variables have a significant positive effect on economic growth.